Administrative Liability for Discrediting the Activities of Public Authorities - D. V. Osintsev (Сибирское юридическое обозрение, 2023)
The subject of the analysis is the relations and activities of law enforcement agencies related to the qualification of administrative offenses aimed at discrediting the Armed Forces of the Russian Federation and state authorities in the context of unfriendly relations and armed confrontation between individual countries.   Forces of the Russian Federation and public authorities in the conditions of unfriendly attitudes and armed confrontation of certain countries.   The purpose of the study is to clarify the phenomenon of verbal and intensional offences of psycho-emotional type, the peculiarities of construction, design and deconstruction of the main elements of the composition of this type of administrative offences.   Clarification of the criteria for the separation of conditionally lawful and categorically unlawful act expressed as a negative statement or aggressive unstable attitude of the psychological state of the person who committed an administrative offence also is the purpose of this paper. The research methods are based on the application of the legal text and correlation of the context of circumstances from the positions of the main provisions of propositional logic (derivation of categorical judgements about the meaning of certain terms with uncertain semantics (discrediting, publicity, targeting, etc.)). The doctrine of multiple predicates (which allowed building of matrix structures of admissibility of imputation of an unlawful act to a subject with a certain legal status only, as well as situational negation of admissibility of its imputation, if a full map of the subject's legal status is not available) is also used in the present research. Besides, design of modal constructions (rules of qualification of administrative offences of psycho-emotional type), as well as the logic of evaluations (in terms of weak and strong statements about prohibited or permissible statements about the activity of representatives of the authorities in certain conditions or in certain ways) is used as effective research method . The main conclusions of the study are expressed in the assertion of the priority establishment of amenability and punishability for offences related to the formation of destructive anti-cultural stereotypes, false ideological attitudes, belittling of the traditional way of life and denial of vital foundations of Russian society, the need to eliminate legal constructions with vague and unclear content. Increased attention should be paid to the semantic analysis and targeting of the offender's phrases precisely to replace the upheld public position with egoistic aspirations and planting the priority of personal misconceptions. It is necessary to introduce a separate category of rules of information and semantic analysis when imputing this or that administrative offence.